KINERJA PEGAWAI DINAS KEBAKARAN DAN PENANGGULANGAN BENCANA KOTA BANDUNG - Disa Nurafiyah; Rita Mryna; Neneng Weti Isnawati (Universitas Padjadjaran, 2022)
Performance plays a role in the organization to encourage performance improvement, and decision making so that the organization has quality resources. This research was conducted on the basis of indications that show the condition of employee performance at the Bandung City Fire and Disaster Management Service, including the condition of human resources that are still lacking in terms of quality and quantity as well as development, indications in terms of cooperation, responsibility and initiatives in work that need to be studied further, as well as the failure to handle several cases of fire disasters in Bandung for the 2017-2020 period. This study aims to answer why the performance of the Bandung Fire and Disaster Management Service, seen from the indications, is still lacking. In this study, the theory used is Mangkunegara's theory of performance indicators of five indicators, namely work quantity, work quality, responsibility, cooperation, and initiative. The research method used in this study is a qualitative descriptive method. The results of this study are the performance of the Bandung Fire and Disaster Management Service is still lacking because there are performance indicators that are still lacking, indicators of quantity, cooperation, and initiative. Indicators that are considered good are in terms of quality and awareness of responsibility. This is reflected in the fulfillment of work standards by all officers in carrying out their duties. Suggestions to improve the performance of the is to establish cooperation with the labor agency, schedule training and development of employees consistently whose form of training can simultaneously improve teamwork and cooperation, and strengthen the unity of horizontal employee relations, Advise consistently and periodically the condition of the officer fleet. In addition, a special budget is needed for fleet maintenance so that it is always primed in carrying out its duties. Kinerja berperan dalam organisasi untuk mendorong perbaikan kinerja, dan pengambilan keputusan sehingga organisasi memiliki sumber daya yang berkualitas. Penelitian ini dilakukan atas indikasi yang menunjukkan kondisi kinerja pegawai pada Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung, diantaranya kondisi sumber daya manusia yang masih kurang dalam aspek kualitas dan kuantias dan pengembangannya, aspek kerjasama, tanggung jawab dan inisiatif dalam bekerja yang perlu dikaji lebih lanjut, dan tidak tertanganinya beberapa kasus bencana kebakaran dalam kurun waktu 2017-2020. Penelitian ini bertujuan untuk menjawab mengapa kinerja Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung dilihat dari indikasinya masih kurang. Dalam penelitian ini teori yang digunakan adalah teori dari Mangkunegara tentang indikator kinerja, yaitu kuantitas kerja, kualitas kerja, tanggung jawab, kerja sama, dan inisiatif. Metode penelitian yang digunakan dalam penelitian ini adalah metode deksriptif kualitatif. Hasil dari penelitian ini adalah Kinerja Pegawai Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung masih kurang karena terdapat indikator kinerja yang masih kurang, diantaranya indikator kuantitas, kerjasama, dan inisiatif. Adapun indikator yang dinilai sudah baik adalah segi kualitas dan kesadaran akan tanggung jawab. Hal tersebut tercermin dari pemenuhan standar kerja oleh seluruh petugas dalam pelaksanaan tugasnya. Saran untuk meningkatkan Kinerja instansi adalah bekerjasama dengan lembaga penyedia tenaga kerja, sehingga dapat menjaring para personil yang memenuhi kualifikasi, Konsisten jadwal pelatihan dan pengembangan yang dapat meningkatkan mempererat kesatuan hubungan horizontal pegawai, Secara konsisten dan berkala mengusulkan mengenai kondisi armada petugas. Selain itu, perlu anggaran khusus perawatan armada agar selalu prima dalam pelaksanaan tugas.